DEVELOPMENT OF CULTURALLY RESPONSIVE MATHEMATICS E-LEARNING: INTEGRATING THE SIKAMBANG TRADITION OF THE BARUS COASTAL COMMUNITY THROUGH THE WORDPRESS PLATFORM - Yumira Simamora; Sahat Saragih; Izwita Dewi; Nur Rahmi Rizqi; Rasida Aulia Sari (JURNAL EDUSCIENCE, 2026)
Purpose - The purpose of this study is to develop culture-responsive mathematics e-learning by integrating the Sikambang Pesisir Barus tradition into the WordPress platform, creating learning that is contextual, meaningful, and relevant to students' cultural backgrounds.Methodology - This research methodology uses a development research (R&D) design with the Plomp model. The research subjects were students/teachers from MTSN 1 and SMP Muhammadiyah 28 Barus, class VII-A, with 24 and 30 students, respectively. The research procedures include the stages of needs analysis, product design and development, expert validation, limited and field trials, and revisions until a valid, practical, and effective product is obtained. The intervention was carried out through the implementation of learning activities on a WordPress-based e-learning platform containing material on quadrilaterals and triangles. The research instruments included expert validation sheets, implementation observation sheets, student response questionnaires, and mathematical literacy ability tests. Data analysis was carried out descriptively and inferentially through tests of validity, practicality, and effectiveness, including n-gain calculations and analyses of learning completeness and student responses.Findings - The results show that a WordPress-based mathematics e-learning integrated with the Sikambang culture meets the criteria for validity, practicality, and effectiveness. The developed media was considered feasible by experts, easy to use in learning, and received positive responses from students. In addition, students' mathematical literacy improved. It can be concluded that integrating local culture into e-learning can make learning more meaningful and engaging.Contribution- These implications and contributions position WordPress as a viable alternative for driving innovative, contextually relevant learning experiences.